2022
DOI: 10.4041/kjod21.153
|View full text |Cite
|
Sign up to set email alerts
|

Which anchorage device is the best during retraction of anterior teeth? An overview of systematic reviews

Abstract: Objective To evaluate the available evidence regarding the clinical effectiveness of different types of anchorage devices. Methods A comprehensive literature search of different electronic databases was conducted for systematic reviews investigating different anchorage methods published up to April 15, 2021. Any ongoing systematic reviews were searched using PROSPERO, and a grey literature search was undertaken using Google Scholar and OpenGrey. No language restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It ensures that the supporting teeth do not move as other teeth are being moved [ 13 ]. Several methods have been proposed to assure good anchorages, such as headgear [ 14 ], transpalatal arches (TPAs), with or without a Nance button [ 15 ], lingual arches, bonding of second molars, or intermaxillary elastics [ 16 ], and most recently, mini-implants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It ensures that the supporting teeth do not move as other teeth are being moved [ 13 ]. Several methods have been proposed to assure good anchorages, such as headgear [ 14 ], transpalatal arches (TPAs), with or without a Nance button [ 15 ], lingual arches, bonding of second molars, or intermaxillary elastics [ 16 ], and most recently, mini-implants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anchorage preparation is considered to be the most important step in clinical orthodontics [13,14]. TADs are recognized to be the prominent anchorage reinforcement devices because of more anchorage preservation than conventional devices [15] and controlled tipping of anterior teeth [16]. This study represented significant improvement of profile in Damon group, which could partly contribute to the low-friction movement and assistance of TADs in half of cases.…”
Section: Discussionmentioning
confidence: 81%
“…Previous study systematically reviewed anchorage methods and found the evidence of a preference of any anchorage method lacked sufficient evidence [15]. Moreover, regarding adverse effects of TADs containing tooth root injury and mucosa lesion [22], the use of TADs may be limited in adolescents or patients who require non-invasive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Enmasse retraction after extraction of maxillary and mandibular premolars may require the use of reinforced anchorage. This could be in the form of conventional anchorage devices such as transpalatal arch, headgear, and Nance appliance; or by the use of temporary anchorage devices (TADS) using miniscrew implants [24,25]. Skeletal anchorage using TADS have resulted in better skeletal, dental and soft tissue changes in bimaxillary protrusion compared to conventional anchorage devices [24,25].…”
Section: Treatmentmentioning
confidence: 99%